Clinical Implementation of Combined Quasi-Static Ultrasound Elastographic and Regional Blood Flow Assessment Techniques, in Areas of Forearm Myofascial Dysfunction, Before and After Osteopathic Physical Manipulation - Pedapati, Chandhana; Keane, James; Durr, Timothy; Heath, Deborah M.; Mast, Douglas; Bay, Curtis; Makin, Inder Raj S. (The Journal of the Acoustical Society of America, 2023)
A fast-growing area of high-resolution ultrasound imaging is localizing painful regions termed myofascial tender points (MTP). To mitigate pain and reduce musculoskeletal nodularity and stiffness, osteopathic physicians perform loco-regional osteopathic manipulative procedures (OMT). Current MTP-diagnostic and clinical efficacy criteria using sono-elastographic, or regional flow biomarkers are poorly characterized. This research aims to develop a well-grounded approach to identify forearm MTPs and track changes post-physical interventions, using elastography combined with regional power Doppler. A 44-subject clinical study cohort, was randomly divided in OMT, mild exercise and “rest” groups: imaging was performed using an open-platform SonixTouch Q + . During controlled tissue deformation (4.5-5 Hz), ultrasound elastography was performed by computing root-main-square (RMS) strain of beamformed ultrasound echoes (13 MHz, 15fps) for 3 s. Similarly, power Doppler maps were averaged over 5 seconds (5–12 fps), to evaluate regional blood flow. Data acquisition and processing sequence was repeated post-intervention. Changes in tissue stiffness as well as regional blood flow were compared pre- and post-intervention for all three human subject groups. With the experimental technique used in this study, a significant reduction in tissue stiffness, and increase in regional blood flow is demonstrated in the OMT group compared to the exercise and rest group.